FPGA-suitable interpolated convolution centroiding algorithms for crossed-strip readout - Zuo, Xiao-Yun; Zheng, Jin-Kun; Duan, Jin-Yao; Yang, Yang; Bai, Yong-Lin (Review of scientific instruments, 2025)
This paper presents a signal readout method for crossed-strip anodes based on an interpolation convolution centroid algorithm. The method determines the channel where the event occurs by grouping and summing comparisons and then performs convolution operations using the corresponding values and convolution kernels. The centroid position of the electron cloud is further calculated through zero-point interpolation. This algorithm significantly improves the readout speed of crossed-strip anode signals while maintaining high-resolution performance. The system's performance is verified through joint simulations using MATLAB and Vivado. Experimental results show that, at the spatial resolution of 22.63 lp/mm, this readout method can achieve an event processing rate exceeding 20 MHz.